Day 1 Mon, November 09, 2020 2020
DOI: 10.2118/202966-ms
|View full text |Cite
|
Sign up to set email alerts
|

Well Completion Optimization in Canada Tight Gas Fields Using Ensemble Machine Learning

Abstract: With the coming of increasingly large databases, the growing amount of computational resources and latest algorithmic advancements, data driven and machine learning techniques are considered as potential game changers in traditional Oil and Gas industry. Unconventional oil and gas formations, including basin central gas/oil, shale gas/oil, tight gas/oil, and coalbed methane formations, are abundant, which have become an increasingly important part of global energy supply and attracted increasing attention from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, some of the I4.0 technologies have been adopted for industrial scale application. For instance, the deployment of AM by Siemens in the production of turbine [256], DT in aweelah Gas Compression Plant in the United Arab Emirates (UAE) [257], ML in optimization of Wapiti horizontal gas well [258], unmanned smart field in United Arab Emirates [259]. In addition, several industry players are already providing digitized services to the O&G by using some of the I4.0 technologies.…”
Section: H Summarymentioning
confidence: 99%
“…However, some of the I4.0 technologies have been adopted for industrial scale application. For instance, the deployment of AM by Siemens in the production of turbine [256], DT in aweelah Gas Compression Plant in the United Arab Emirates (UAE) [257], ML in optimization of Wapiti horizontal gas well [258], unmanned smart field in United Arab Emirates [259]. In addition, several industry players are already providing digitized services to the O&G by using some of the I4.0 technologies.…”
Section: H Summarymentioning
confidence: 99%
“…We selected these algorithms due to their proven effectiveness in handling high-dimensional data and capturing the complex non-linear relationships inherent in reservoir and production data. These models are particularly adept at dealing with the imbalanced and noisy nature of the datasets typically encountered in gas production prediction tasks [29][30][31][32]. By integrating geological, reservoir, engineering parameters, and production data, several basic models for predicting the production in unconventional gas single wells was established, and the accuracy of each model was validated.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging machine learning technique has provided a potential method for production modeling as a result of advanced computing powers and access to large data set. Liao et al [10] used random forest, Extreme Gradient Boosting (XGBoost), and Light Gradient Boosting Machine (LGBM) to build a stacking model and identified that stimulated length, total stage count, pumped proppant per stage, pumped fluid per length and injection rate are the most important factors for Wapiti-Montney tight gas formation. However, the model did not include reservoir parameters such as total organic carbon content (TOC).…”
Section: Introductionmentioning
confidence: 99%